Khazanah Al-Qur’an Kuno Bangkalan Madura - Hakim, Abdul (SUHUF, 2015)
Bangkalan is one of four Islamic of cultural centers in Madura. One of its heritage is the ancient Qur’an of Bangkalan palace. There are 56 ancient manuscripts of the ancient Qur’an which are stored in the Great Mosque of Bangkalan. This paper examines only 6 manuscripts namely 3 manuscripts of 30 chapters and 3 chapters of the one third of the manuscript. The focus of the study lies on several manuscripts colophon. The study found that the ancient Qur’an has a connection with the royal presence Bangkalan based on the cover of the logo cover in form of chakra symbol in octagonal form, the names listed on the colophon and their dates. Keywords: Quranic manuscript, Colophon, Bangkalan, Madura.